PENGARUH IMPLEMETASI PENGENDALIAN INTERNAL DAN KOMPETENSI PENGELOLA TERHADAP EFEKTIVITAS MANAJEMEN ASET TETAP PADA PERGURUAN TINGGI NEGERI BERBADAN HUKUM - Syarbini Ikhsan, Sabirin. (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2020)
This study aims to analyze the effect of the Implementation of Internal Control and Manager  Competence  on  the  Effectiveness  of  Fixed  Asset  Management  in  State Universities as Legal Entities partially or simultaneously. The population in this study is the Legal Entity State Universities in Indonesia, amounting to eleven. The sampling technique is saturated or census sampling. This research uses a quantitative approach with multiple regression analysis techniques. The results of the research show that the implementation of internal control and managerial competence has a significant positive effect on the effectiveness of fixed asset management, in Indonesian legal institutions both partially and simultaneously.Key Word: Implementation of Internal Control, Manager Competence and Effectiveness of Fixed Asset Management